nDrop2exel - Roylands, Johannes (SciLifeLab Serve, 2026)
This application: XPS Files: Converts XPS to PDF using xpstopdf (requires libgxps-utils) PDF Files: Extracts tables using advanced table detection Number Format: Handles Swedish format (comma as decimal separator) Table Merging: Automatically merges fragmented tables from multiple pages Excel Export: Saves each file's tables to separate Excel sheets Summary: Optionally creates a combined summary with Sample, ng/ul, and 260/280 data Supported formats: PDF files with tables XPS files (converted to PDF first) Output: Individual Excel files for each input file Combined summary Excel file (optional) ZIP download for multiple files